Reversing the relative 3MLCT–3MC order in Fe(ii) complexes using cyclometallating ligands: a computational study aiming at luminescent Fe(ii) complexes1. Issue 30 (14th August 2015) - Dixon, Isabelle M.; Alary, Fabienne; Boggio-Pasqua, Martial; Heully, Jean-Louis
<x xml:space="preserve">Abstract</x> Positioning two cyclometallating rings on the periphery of tridentate ligands has allowed us to design for the first time an iron(ii) complex bearing the lowest triplet state of MLCT nature.